2021
DOI: 10.1177/19389655211016831
|View full text |Cite
|
Sign up to set email alerts
|

Looks Clear and Sounds Familiar: How Consumers Form Inferential Beliefs About Luxury Hotel Service Quality

Abstract: The purpose of this study is to examine how varying levels of brand familiarity and photographic image quality of hotel pictures influence consumers’ perceptions about luxury hotel services and attitudinal responses and whether their visual aesthetic experience and inferential beliefs about service quality can mediate such effects. This is a 2 (brand familiarity: familiar vs. unfamiliar brand) × 2 (image quality: high vs. low image resolution) factorial design randomized experiment and the proposed model was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…In the context of reviews, we expect two integral factors to be particularly relevant to reducing processing ease and hence to attenuate or even eliminate the effect of content similarity on helpfulness: review text difficulty and photo quality. A harder-to-read text (Shulman et al 2020) can make the review text more difficult to parse, and low-quality images impair visual assessment (Ryu, Park, and Park 2022). In summary, we expect factors that hamper processing ease to attenuate the effect of content similarity on helpfulness (compared with the absence of such impediments).…”
Section: Limits Of Similarity-driven Effects On Helpfulnessmentioning
confidence: 99%
“…In the context of reviews, we expect two integral factors to be particularly relevant to reducing processing ease and hence to attenuate or even eliminate the effect of content similarity on helpfulness: review text difficulty and photo quality. A harder-to-read text (Shulman et al 2020) can make the review text more difficult to parse, and low-quality images impair visual assessment (Ryu, Park, and Park 2022). In summary, we expect factors that hamper processing ease to attenuate the effect of content similarity on helpfulness (compared with the absence of such impediments).…”
Section: Limits Of Similarity-driven Effects On Helpfulnessmentioning
confidence: 99%
“…To enhance the image the hotel has thrusted upon the waiters and hotel employees and their educational backgrounds and customer dealing abilities (Setia, et, al, 2021). Ryu et. al, 2022 have found that there exist a correlation between service quality and hotel name and image.…”
Section: Service Quality Effect On Brand Name and Brand Imagementioning
confidence: 99%
“…However, if the price is set high with low performance, customers will likely switch to other service providers, harming the hotel. [15] show the results of exploring various hotel brand and image levels mediated by service quality, which impacts customer selection. One aspect in determining service selection is price comparisons based on customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%